Harmonization of Automation and Fire Alarm System Teaching Materials: an Effort to Improve the Quality of Aviation Safety Education - Wartoyo, Bayu Purbo; Suhanto, Suhanto; Driyono, Bambang; Novita, Sheilla; Nugrah, Andi Fadhilah (Formosa Journal of Applied Sciences, 2025)
This study aims to achieve harmonization of Course Learning Outcomes (CPMK) through standardization of teaching materials at UPT PPSDMPU in the Air Navigation Technology Study Program, and improve the competence of cadets with teaching material books. The method used is the S. Thiagrajan development model modified from 4-D to 3-D, with a focus on the Development stage (Develop) to produce learning modules that are valid and ready to be implemented, as well as for time and cost efficiency. The results showed that the learning module developed was declared valid by expert validators, met the criteria of very practical based on student responses, and proved effective through pre-test and post-test tests, so it is feasible to use in the learning process to support the quality of education.